Editorial Board and Guidelines for the Authors, SUSURGALUR Journal, Issue of March 2016 - SUSURGALUR, Editor Journal (SUSURGALUR, 2016)
SUSURGALUR journal will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the history education and historical studies in general and its various aspects. Analysis will be practical and rigorous in nature. The SUSURGALUR journal, with Print ISSN 2302-5808, was firstly published on March 24, 2013, in the context to commemorate the BLA (Bandung Lautan Api or Bandung a Sea of Flames)âs Day in Indonesia. Since issue of September 2013 to date, the SUSURGALUR journal has jointly been organized by the Lecturers of APB UBD (Academy of Brunei Studies, University of Brunei Darussalam) and the Lecturers of International and Historical Study Program FASS (Faculty of Arts and Social Sciences) UBD in Bandar Seri Begawan, Brunei Darussalam; and published by Minda Masagi Press as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. This journal is published twice a year i.e. every March and September.Â Bandar Seri Begawan, Brunei Darussalam: March 24, 2016.Assoc. Prof. Awang Dr. Haji Asbol bin Haji MailVice Chief Editor of the SUSURGALUR Journal in Bandung, Indonesia; and Senior Lecturer at the International History Program, Faculty of Arts and Social Sciences UBD (University of Brunei Darussalam) in Bandar Seri Begawan, Brunei Darussalam.Â